ANALISIS PERTIMBANGAN KOMISI PENGAWAS PERSAINGAN USAHA TERHADAP PELANGGARAN OLEH PERUSAHAAN PENERBANGAN BADAN USAHA MILIK NEGARA (STUDI PUTUSAN No. 15/KPPU-I/2019) - Faisal Fachri; Iwan Joesoef (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2020)
The purpose of this research to understand the monopoly concept carried out by state-owned enterprises in the aviation sector and efforts to overcome it. The method used in this study is a normative juridical approach using secondary data, namely data obtained from literature reviews. The type of research carried out in this paper is legal research, namely research that examines the formulation of problems contained in research by examining the relevant laws and regulations that apply. The conclusion of this research is that State-Owned Enterprises are state-owned companies that are granted exemptions to monopolize market share for the benefit and welfare of the people. The per se illegal approach method is used to determine the impact of an alleged violation of business competition. Good corporate governance can be used as a reference in determining any actions taken by State-Owned Enterprises in market share to encourage or inhibit competition.